If one of them and the other One is exactly the same(capital,letters) then it is equal:D
no
x^2/y^3 = x^2*y^(-3)
0
Neither y3x-3 nor 3x-y3 are equations, and so neither of them can have a solution. Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. And using ^ to indicate powers (eg x-squared = x^2).
(x + y)3 + (x - y)3 = (x3 + 3x2y + 3xy2 + y3) + (x3 - 3x2y + 3xy2 - y3) = 2x3 + 6xy2 = 2x*(x2 + 3y2)
y3 x y3 - y (3)3 x 3(3) - 3 9 x 9 - 3 = ? 9 x 9= 81 81 - 3 = 78 I hope that solves your problem
no
Assuming that your question is x - y^3 Then you would do the following: x = -10 y = -3 -10 - (-3)^3 -10 - (-27) -10 + 27 = 17
x^2/y^3 = x^2*y^(-3)
0
Neither y3x-3 nor 3x-y3 are equations, and so neither of them can have a solution. Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. And using ^ to indicate powers (eg x-squared = x^2).
(x + y)3 + (x - y)3 = (x3 + 3x2y + 3xy2 + y3) + (x3 - 3x2y + 3xy2 - y3) = 2x3 + 6xy2 = 2x*(x2 + 3y2)
6x+y=3
0
The second would suggest that x equals the string "=3".
x + 3 = 2x 3 = x x cannot be 2
Y3